Antibacterial activities of tannic acid against isolated ruminal bacteria from sheep. (April 2018) - Cipriano-Salazar, Moisés; Rojas-Hernández, Saúl; Olivares-Pérez, Jaime; Jiménez-Guillén, Régulo; Cruz-Lagunas, Blas; Camacho-Díaz, Luis Miguel; Ugbogu, Amadike Eziuche
Abstract: This present study was conducted to evaluate the antimicrobial effects of tannic acid (TA) against isolated ruminal bacteria from adult sheep. Rumen samples were collected from two (2) adults sheep, and a total of nine (9) ruminal bacteria were isolated from the sample. The sensitivity of the ruminal bacteria isolates to 0.63, 1.25, 2.50, 5.00 and 10.00 mg TA/mL of growth medium was determined using clearance zone (CZ) of Kirby-Bauer disc diffusion susceptibility test. There was observable increase in the sensitivity of all bacterial isolates as the level of TA increases. Not all bacterial isolates have the capacity to tolerate more than 1.25 mg TA/mL. The result shows that only 20% of the bacterial isolates had the capacity to tolerate 0.63 and 1.25 mg of tannic acid per liter. This concentration of tannic acid would be equivalent to 2% tannin in the diet of ruminant. Our findings shows that increase in concentration of tannic acid completely inhibited the ruminal bacteria from the sheep rumen. Highlights: Tannic acid is an efficient antimicrobial agent against ruminal bacteria isolated from adult sheep. Only 20% of ruminal bacteria isolated from adult sheep had the capacity to survive up to 1.25 mg of tannic acid. Ruminal bacteria isolated from adult sheep had zero tolerance to tannic acid between 2 and 10 mg of tannic acid. Tannic acid ranging from 0–1.25 mg/mL can be used to modify microbial activities and enhance feed utilization in ruminants.